(untitled) (Proceedings of International Educators Conference, 2024)
This article defines the concept of LLC in the current legislation, in this regard, the existing problems and proposals, as well as issues of legal status and scope of responsibility of its participants, different approaches of scholars and issues related to improving the civil law of the LLC, the legislation of the Republic of Uzbekistan. Scientific and theoretical problems of the civil-legal status of the LLC, the concept and essence of the LLC, its role and importance in the system of civil law entities, legal entities and business societies, the legal basis for the formation and reorganization of the LLC and its problems. Also analyzed the activities of the LLC, the legal status of the participants of the LLC, property and property rights of the LLC, civil liability of the LLC, the constituent documents of the LLC and their registration, the specifics of the legal and legal capacity of the LLC. In addition, the relationShip between foreign joint stock companies and limited liability companies was studied. The novelty of the study is the study of a wide range of problems, as well as scientifically based and important practical recommendations for improving the legislation in the field of civil regulation of the LLC.